Positive electrode active material, manufacturing method thereof, and non-aqueous electrolyte secondary battery including positive electrode active material
A coated Ni-containing lithium transition metal composite oxide with a Co and Mn composite oxide layer addresses the need for improved input/output and cycle characteristics in non-aqueous electrolyte secondary batteries, particularly for vehicle applications, by suppressing electrolyte reaction and Li movement.
Patent Information
- Application Number
- JP2023113743
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-11
AI Technical Summary
Non-aqueous electrolyte secondary batteries, particularly those used in high input/output power storage devices for vehicles, require improvements in both input/output characteristics and cycle characteristics to meet the demands of modern applications.
A positive electrode active material is developed by coating a particulate Ni-containing lithium transition metal composite oxide with a composite oxide layer containing Co and Mn, with a thickness of 50 to 200 nm, which is formed through a firing process at 500°C to 800°C in an oxygen atmosphere, to suppress electrolyte reaction and enhance Li movement.
The solution achieves a non-aqueous electrolyte secondary battery with improved input/output characteristics and cycle characteristics by reducing reaction with the electrolyte and inhibiting Li movement, thereby enhancing battery performance.
Smart Images

Figure 2025011557000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material, a method for producing the same, and a nonaqueous electrolyte secondary battery including the positive electrode active material. [Background technology]
[0002] Lithium transition metal composite oxides are widely used as positive electrode active materials for non-aqueous electrolyte secondary batteries. In recent years, in order to improve battery characteristics, the surface of particulate lithium transition metal composite oxides has been coated with a compound containing tungsten (see Patent Documents 1 to 4). In this regard, for example, Patent Document 1 discloses a method for producing a positive electrode active material, which includes a step of mixing a Ni-containing lithium transition metal composite oxide with nickel tungstate to obtain a mixture, and a step of drying the mixture at, for example, 150°C. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-133839 A [Patent Document 2] JP 2010-040383 A [Patent Document 3] International Publication No. 2013 / 015069 [Patent Document 4] International Publication No. 2015 / 141194 Summary of the Invention [Problem to be solved by the invention]
[0004] As non-aqueous electrolyte secondary batteries become more widespread, there is a demand for further improvements in their performance. In particular, high-input / output type electricity storage devices mounted on mobile objects such as vehicles are required to have both high-level input / output characteristics and high-level cycle characteristics.
[0005] The present invention has been made in view of the above circumstances, and a main object of the present invention is to provide a positive electrode active material capable of realizing a nonaqueous electrolyte secondary battery having both high levels of input / output characteristics and cycle characteristics. [Means for solving the problem]
[0006] The present invention provides a positive electrode active material comprising a particulate Ni-containing lithium transition metal composite oxide and a coating layer attached to at least a portion of the surface of the Ni-containing lithium transition metal composite oxide, the coating layer including a composite oxide containing a first element selected from Co and Mn, and a second element belonging to Group 6, and having an average thickness of 50 nm or more and 200 nm or less as determined by cross-sectional observation with a transmission electron microscope.
[0007] By providing the particulate Ni-containing lithium transition metal composite oxide with the coating layer, the reaction with the electrolyte can be suppressed, and excellent cycle characteristics can be realized. In addition, by setting the thickness of the coating layer to a predetermined value or less, Li migration is less likely to be hindered, and excellent input / output characteristics can be realized. Therefore, according to the above configuration, a nonaqueous electrolyte secondary battery having both high levels of input / output characteristics and cycle characteristics can be suitably realized.
[0008] The present invention also provides a method for producing a positive electrode active material, which includes a mixing step of mixing a particulate Ni-containing lithium transition metal composite oxide with a compound containing a first element selected from Co and Mn and a second element belonging to group 6 to obtain a mixture, and a firing step of firing the mixture in the presence of oxygen at a temperature of 500° C. to 800° C. This makes it possible to suitably produce the above-mentioned positive electrode active material. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic diagram of a positive electrode active material according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic internal structure of a nonaqueous electrolyte secondary battery according to one embodiment. [Diagram 3]FIG. 3 is a cross-sectional SEM image of the positive electrode active material of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, some preferred embodiments of the present invention will be described with reference to the drawings as appropriate. Matters other than those specifically mentioned in this specification and necessary for carrying out the present invention (for example, the general configuration and manufacturing process of a non-aqueous electrolyte secondary battery that does not characterize the present invention) can be understood as design matters of a person skilled in the art based on the prior art in the field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the field.
[0011] In the following drawings, the same reference numerals are used for components and parts that perform the same function, and duplicated explanations may be omitted or simplified. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery in general that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with lithium ions between positive and negative electrodes. In addition, the expression "A to B" indicating a range in this specification includes the meaning of "A or more and B or less," as well as "preferably larger than A" and "preferably smaller than B."
[0012] [Cathode active material] Fig. 1 is a cross-sectional view showing a schematic diagram of a positive electrode active material 1 according to one embodiment. The positive electrode active material 1 includes a Ni-containing lithium transition metal composite oxide 2 serving as a base material, and a coating layer 4 attached to at least a part of the surface of the Ni-containing lithium transition metal composite oxide 2. The coating layer 4 is typically attached to the Ni-containing lithium transition metal composite oxide 2 by physical and / or chemical bonding. The coating layer 4 is preferably fused to the Ni-containing lithium transition metal composite oxide 2. Note that Fig. 1 is merely an example and is not limited to what is shown in the figure.
[0013] The Ni-containing lithium transition metal composite oxide 2 is a composite oxide containing Li and Ni as essential elements. Specific examples of the Ni-containing lithium transition metal composite oxide 2 include lithium nickel composite oxide, lithium nickel cobalt composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide. These may be used alone or in combination of two or more. The Ni-containing lithium transition metal composite oxide 2 preferably further contains at least one of Co and Mn in addition to Ni. Among them, lithium nickel cobalt manganese composite oxide containing Ni, Co, and Mn is preferred because it has excellent battery characteristics such as low initial resistance.
[0014] In this specification, the term "lithium nickel cobalt manganese composite oxide" includes oxides containing Li, Ni, Co, Mn, and O as constituent elements, as well as oxides containing one or more additional elements other than those. Examples of such additional elements include transition metal elements and typical metal elements such as Mg, Ba, Sr, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, K, Fe, Cu, Zn, and Sn. The additional element may be a semimetal element such as B, C, Si, or P, or a nonmetal element such as S, F, Cl, Br, or I. This also applies to the above-mentioned lithium nickel composite oxide, lithium nickel cobalt composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.
[0015] From the perspective of improving the energy density of the battery, the lithium nickel cobalt manganese composite oxide preferably contains a high-Ni-containing lithium transition metal composite oxide in which the Ni content is set as high as 70 mol% or more relative to the total of metal elements other than lithium. The Ni content is preferably 75 mol% or more, for example, 80 mol% or more. According to the findings of the present inventors, the high-Ni-containing lithium transition metal composite oxide is relatively likely to have deteriorated cycle characteristics compared to the lithium composite oxide with a low Ni content. Therefore, it is particularly effective to apply the technology disclosed herein.
[0016] The lithium nickel cobalt manganese composite oxide preferably has a composition represented by the following formula (I). Li α Ni x Mn y Co z M t O2 (I) In the above formula (I), α, x, y, z, and t each satisfy 1.00 ≤ α ≤ 1.30, 0.25 < x < 0.90, 0 < y < 0.60, 0 < z < 0.60, 0 ≤ t ≤ 0.10, and x + y + z + t = 1. When 0 < t, M is at least one element selected from the group consisting of Mg, Ca, Al, Ti, V, Cr, Fe, Cu, Zn, Zr, Nb, Mo, Ta, and W.
[0017] α preferably satisfies α ≤ 1.20, more preferably satisfies α ≤ 1.10. From the perspective of improving battery characteristics (for example, input / output characteristics and cycle characteristics), x preferably satisfies 0.5 ≤ x, more preferably satisfies 0.7 ≤ x, for example, 0.8 ≤ x ≤ 0.9, y preferably satisfies 0.01 ≤ y, more preferably satisfies 0.03 ≤ y ≤ 0.20, for example, 0.05 ≤ y ≤ 0.1, z preferably satisfies 0.01 ≤ z ≤ 0.50, more preferably satisfies 0.05 ≤ z ≤ 0.30, for example, 0.10 ≤ z ≤ 0.20. t preferably satisfies 0 ≤ t ≤ 0.05, more preferably is 0.
[0018] The Ni-containing lithium transition metal composite oxide 2 preferably has a layered rock salt type crystal structure. Examples of lithium composite oxides having such a crystal structure include lithium nickel cobalt manganese composite oxides and lithium nickel cobalt aluminum composite oxides. However, the crystal structure of the Ni-containing lithium transition metal composite oxide 2 may be a spinel structure or the like. The crystal structure can be confirmed by X-ray diffraction or the like.
[0019] In Fig. 1, the Ni-containing lithium transition metal composite oxide 2 is in the form of particles. The shape of the Ni-containing lithium transition metal composite oxide 2 is not particularly limited, but is generally spherical here. However, it may be of an indefinite shape or the like. In this specification, "approximately spherical" refers to a shape that can be regarded as roughly a sphere as a whole, and an average aspect ratio (major axis / minor axis ratio) based on a cross-sectional observation image with an electron microscope is roughly 1 to 2, for example, 1 to 1.5.
[0020] In some embodiments, the Ni-containing lithium transition metal composite oxide 2 is preferably in the form of secondary particles formed by agglomeration of a plurality of primary particles by physical or chemical bonding force. The Ni-containing lithium transition metal composite oxide 2 (i.e., secondary particles) is preferably an aggregate of primary particles in which a large number of primary particles are aggregated to form one particle. In this specification, the term "primary particle" refers to the smallest unit of particles constituting the Ni-containing lithium transition metal composite oxide 2, specifically, the smallest unit determined from the geometric shape of the appearance. The number of primary particles constituting one secondary particle is typically 10 or more, for example, 20 or more, preferably 100 or more, and more preferably several hundred or more. The number of primary particles in one secondary particle can be confirmed by observing the secondary particle at a magnification of 10,000 to 30,000 times using an electron microscope (e.g., scanning electron microscope).
[0021] Although not particularly limited, when the Ni-containing lithium transition metal composite oxide 2 is in the form of secondary particles, the average particle diameter (D50) of the secondary particles is preferably 1 to 50 μm, more preferably 3 to 30 μm, from the viewpoint of improving battery characteristics (e.g., input / output characteristics and cycle characteristics). In this specification, the term "average particle diameter (D50)" refers to the median diameter (D50) and means the particle diameter corresponding to a cumulative frequency of 50 volume % from the fine particle side with a small particle diameter in a volume-based particle size distribution based on a laser diffraction / scattering method.
[0022] The average primary particle diameter of the primary particles constituting the secondary particles is preferably 0.1 to 2 μm or more, more preferably 0.2 to 1 μm, and particularly preferably 0.4 to 0.5 μm, from the viewpoint of suitably increasing the mechanical strength of the secondary particles and the cycle characteristics of the battery. In this specification, the term "average primary particle diameter" refers to the average value of the major axes of a plurality of (e.g., 10 or more) primary particles grasped from the cross-sectional observation image and arbitrarily selected. The average primary particle diameter can be determined, for example, by using image analysis type particle size distribution measurement software (e.g., "Mac-View") to determine the major axes of a plurality of primary particles arbitrarily selected from the cross-sectional observation image and calculating the average value.
[0023] In some embodiments, the Ni-containing lithium transition metal composite oxide 2 may be in the form of a single particle. In this specification, the term "single particle" refers to a particle generated by the growth of a single crystal nucleus, and thus a single crystal particle that does not include a crystal grain boundary. The number of primary particles constituting one single particle is typically less than 10, for example, about 2 to 5. The fact that the particle is a single crystal can be confirmed, for example, by analysis of an electron beam diffraction image using an electron microscope (for example, a scanning electron microscope).
[0024] The coating layer 4 is attached to at least a part of the surface of the Ni-containing lithium transition metal composite oxide 2, and constitutes at least a part of the outer surface of the positive electrode active material 1. The coverage of the Ni-containing lithium transition metal composite oxide 2 with the coating layer 4 is preferably 50% or more, more preferably 80% or more, and particularly preferably 95% or more (i.e., substantially covering the entire Ni-containing lithium transition metal composite oxide 2). Note that the fact that the coating layer 4 is attached to the surface of the secondary particles and the proportion of the portion covered with the coating layer 4 (coverage) can be confirmed by, for example, subjecting the positive electrode active material 1 to X-ray photoelectron spectroscopy (XPS) analysis described below.
[0025] The coating layer 4 includes a composite oxide (hereinafter, also referred to as a "coating oxide") including a first element and a second element. The first element is cobalt (Co) and / or manganese (Mn). The first element preferably includes Co, and more preferably is Co. This allows the input / output characteristics and cycle characteristics to be balanced at a higher level, and the effects of the technology disclosed herein can be exhibited at a higher level. The second element includes at least one element belonging to Group 6 (chromium group), such as chromium (Cr), molybdenum (Mo), and tungsten (W). Among these, it preferably includes W, and more preferably is W. This allows the input / output characteristics and cycle characteristics to be balanced at a higher level, and the effects of the technology disclosed herein can be exhibited at a higher level.
[0026] The coating oxide preferably has a composition represented by the following formula (II). Ae 1 Ae 2 O4(II) Ae in the above formula (II) 1 is the first element, and Ae 2 is the second element. Specific examples of the coating oxide include CoWO4, MnWO4, CoCrO4, MnCrO4, CoMoO4, and MnMoO4.
[0027] The coating layer 4 may be composed of the coating oxide described above, or, for example, a portion of the coating layer 4 close to the Ni-containing lithium transition metal composite oxide 2 may contain a compound (e.g., a Li compound) containing an element derived from the Ni-containing lithium transition metal composite oxide 2. The proportion of the coating oxide in the entire coating layer 4 is, on a mass basis, preferably 80 mass % or more, more preferably 90 mass % or more, and particularly preferably 95 mass % or more (i.e., the coating layer 4 is substantially composed of the coating oxide).
[0028] The coating layer 4 has an average thickness of 50 to 200 nm based on cross-sectional observation by a transmission electron microscope. By setting the average thickness to a predetermined value or more, the reaction with the electrolyte can be suitably suppressed. As a result, even if charging and discharging are repeated, the growth of a solid electrolyte interface (SEI) film is suppressed, and the cycle characteristics of the battery can be appropriately improved. From this viewpoint, the average thickness of the coating layer 4 is preferably 60 nm or more, more preferably 80 nm or more, and particularly preferably 100 nm or more. Furthermore, by setting the average thickness to a predetermined value or less, the Li movement of the Ni-containing lithium transition metal composite oxide 2 is less likely to be hindered, so that the resistance of the positive electrode can be reduced and the input / output characteristics of the battery can be appropriately improved. From this viewpoint, the average thickness of the coating layer 4 is preferably 190 nm or less, more preferably 170 nm or less, and particularly preferably 150 nm or less.
[0029] It is preferable that the coating layer 4 does not substantially contain WO3. This makes it difficult for Li migration in the Ni-containing lithium transition metal composite oxide 2 to be hindered, thereby improving the battery characteristics (e.g., energy density and input / output characteristics). It is preferable that the coating layer 4 does not substantially contain LiWO4. This makes it possible to suppress the elution of Li from the Ni-containing lithium transition metal composite oxide 2, thereby improving the battery characteristics (e.g., cycle characteristics).
[0030] The coating layer 4 is preferably substantially free of Ni element. The coating layer 4 is preferably substantially free of NiWO4 as described in Patent Document 1. According to the study by the present inventors, when NiWO4 is contained, Ni and Li react with each other in the firing step (2) of the manufacturing method described below, and Ni migrates to the Li layer, which is called cation mixing, and this may occur. By being substantially free of NiWO4, the battery characteristics (e.g., energy density and cycle characteristics) can be improved. In this specification, the term "substantially free" is a term that allows the target component to be contained in a very small amount as long as it does not significantly impair the effects of the technology disclosed herein, and means that the ratio of the target component in the coating layer 4 is less than 1 mass %, for example.
[0031] When the coating layer 4 does not substantially contain Ni, the positive electrode active material 1 is measured by XPS analysis in a region from the outermost surface to a depth of 10 nm, and in this region, when the total of the transition metal element contained in the Ni-containing lithium transition metal composite oxide 2 and the first element and the second element contained in the coating layer 4 is taken as 100 mol%, the ratio of the Ni element is preferably about 3 mol% or less, and preferably 1 mol% or less. In the XPS analysis, it is more preferable that the Ni element is below the lower limit of detection. The ratio of the Ni element is an index representing the thickness of the coating layer 4. The ratio of the Ni element being a predetermined value or less (preferably below the lower limit of detection) indicates that the thickness of the coating layer 4 is 10 nm or more. The ratio of the Ni element being a predetermined value or less can further improve the cycle characteristics of the battery. Note that detailed measurement conditions for the XPS analysis will be shown in the examples described later.
[0032] When the coating layer 4 does not substantially contain Ni, the positive electrode active material 1 is observed in a range of 3 μm long x 3 μm wide on the surface by a scanning electron microscope (SEM), and element mapping is performed by energy dispersive X-ray (EDX) analysis. In this range, when the total of the transition metal element contained in the Ni-containing lithium transition metal composite oxide 2 and the first element and the second element contained in the coating layer 4 is 100 mol%, the ratio of the Ni element is preferably about 10 mol% or less, more preferably 5 mol% or less. The ratio of the Ni element is the ratio of the Ni-containing lithium transition metal composite oxide 2 exposed on the outermost surface of the positive electrode active material 1, in other words, an index indicating the variation in the coating of the coating layer 4. In other words, the ratio of the Ni element being a predetermined value or less indicates that the coverage rate of the Ni-containing lithium transition metal composite oxide 2 by the coating layer 4 is high, and the coating layer 4 is evenly coated on the Ni-containing lithium transition metal composite oxide 2. By controlling the proportion of Ni element to a predetermined value or less, the cycle characteristics of the battery can be further improved. Note that detailed measurement conditions for the SEM-EDX analysis will be shown in the examples described later.
[0033] [Method for producing positive electrode active material] The above-described positive electrode active material 1 can be suitably produced by a production method including, for example, (1) a mixing step and (2) a firing step in this order. The production method disclosed herein may further include other steps at any stage.
[0034] (1) The mixing step is a step of mixing a particulate Ni-containing lithium transition metal composite oxide 2 as a base material with a coating oxide source to obtain a mixture. The mixing method is not particularly limited, and a conventionally known dry mixing method or wet mixing method can be adopted. From the viewpoint of simplicity and cost, the dry mixing method is preferred. The dry mixing can be performed by a conventionally known method, for example, a jet mill, a ball mill, a planetary mixer, a disperser, a mortar, etc. In addition, in the dry mixing, ethanol may be appropriately added as a dispersant so that the coating oxide source is more uniformly coated. The particulate Ni-containing lithium transition metal composite oxide 2 can be produced by a conventionally known method (for example, a crystallization method), or may be prepared by purchasing a commercially available product. The coating oxide source is a compound containing a first element selected from Co and Mn and a second element belonging to Group 6. The coating oxide source may be an oxide. Examples of the coating oxide source include CoWO4, MnWO4, etc.
[0035] The mixing ratio of the Ni-containing lithium transition metal composite oxide 2 and the coating oxide source may be determined so that the thickness of the coating layer 4 is a desired value, for example, 50 to 200 nm. Although it may vary depending on the average particle size of the Ni-containing lithium transition metal composite oxide 2, for example, in order to make the thickness of the coating layer 4 about 10 nm, it is preferable to add about 0.01 mass % (100 ppm) of the coating oxide source to the Ni-containing lithium transition metal composite oxide 2, in order to make the thickness of the coating layer 4 about 100 to 150 nm, it is preferable to add about 0.1 mass % (1000 ppm) of the coating oxide source to the Ni-containing lithium transition metal composite oxide 2, and in order to make the thickness of the coating layer 4 about 1000 nm, it is preferable to add about 1 mass % (10000 ppm) of the coating oxide source to the Ni-containing lithium transition metal composite oxide 2.
[0036] (2) The firing step is a step of firing the mixture obtained in the mixing step at a temperature of 500 to 800°C in the presence of oxygen. According to the study by the present inventors, the firing temperature is set to 500°C or higher, whereby the coating oxide source can be suitably melted and fused to the surface of the Ni-containing lithium transition metal composite oxide 2. Therefore, compared to the case of performing low-temperature coating at 150°C as described in Patent Document 1, for example, the unevenness in the formation of the coating layer 4 can be relatively reduced and the coverage can be increased. In addition, the coating layer 4 with less variation can be formed. From this viewpoint, the firing temperature is preferably 600°C or higher, more preferably 700°C or higher. The upper limit of the firing temperature is preferably about 900°C or lower, for example, 850°C or lower, from the viewpoint of lithium reduction due to lithium volatilization during high-temperature firing and growth of secondary particles. The firing time is preferably about 1 to 24 hours, preferably 5 to 12 hours. The temperature rise rate is preferably, for example, 5 to 40°C / min. The firing atmosphere is preferably an oxygen-containing atmosphere, for example, an oxygen atmosphere or an air atmosphere. In this manner, the coating oxide is attached to the surface of the Ni-containing lithium transition metal composite oxide 2 as the base material, and the positive electrode active material 1 disclosed herein can be produced.
[0037] [Nonaqueous electrolyte secondary battery] Fig. 2 is a cross-sectional view showing a schematic internal structure of a nonaqueous electrolyte secondary battery 100 according to an embodiment. The nonaqueous electrolyte secondary battery 100 shown in Fig. 2 is a prismatic battery in which a flat electrode body 20 and a nonaqueous electrolyte 80 are housed and sealed in a flat prismatic battery case 30. Note that Fig. 2 is an example and is not limited to the one shown in the figure. In other embodiments, the nonaqueous electrolyte secondary battery may be a coin type, a button type, a cylindrical type, a laminated case type, or the like.
[0038] The battery case 30 is an exterior container that houses the electrode assembly 20 and the non-aqueous electrolyte 80. The battery case 30 is made of a lightweight metal material with good thermal conductivity, such as aluminum. On the outer surface of the battery case 30, a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher, are provided. The positive electrode terminal 42 is electrically connected to a positive electrode current collector 42a, and the negative electrode terminal 44 is electrically connected to a negative electrode current collector 44a.
[0039] Here, the electrode body 20 is a wound electrode body in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two strip-shaped separator sheets 70 interposed therebetween and wound in the longitudinal direction. However, in other embodiments, the electrode body may be a laminated electrode body in which a rectangular positive electrode and a rectangular negative electrode are laminated with a rectangular separator interposed therebetween. As shown in a partially cutaway view in FIG. 2, the positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a strip-shaped positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a strip-shaped negative electrode current collector 62.
[0040] At both ends of the electrode body 20 in the winding axis direction (i.e., the width direction perpendicular to the longitudinal direction), a positive electrode active material layer non-forming portion 52a where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed, and a negative electrode active material layer non-forming portion 62a where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed are formed so as to protrude outward. The positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a each function as a current collector. The positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a are provided with a positive electrode current collector 42a and a negative electrode current collector 44a, respectively. The shapes of the positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a are not limited to those shown in the figures. The positive electrode active material layer-free portion 52a and the negative electrode active material layer-free portion 62a may be formed as current collecting tabs processed into a predetermined shape.
[0041] The positive electrode current collector 52 is strip-shaped. The positive electrode current collector 52 is preferably made of metal, and more preferably made of metal foil. The positive electrode current collector 52 is an aluminum foil in this embodiment. The positive electrode active material layer 54 contains at least the above-mentioned positive electrode active material 1. The positive electrode active material layer 54 may contain a type of positive electrode active material other than the above-mentioned positive electrode active material 1. When the entire positive electrode active material contained in the positive electrode active material layer 54 is taken as 100% by mass, the proportion of the above-mentioned positive electrode active material 1 is approximately 50% by mass or more, preferably 60% by mass or more, more preferably 80% by mass or more, for example, 85 to 100% by mass. This allows the effects of the technology disclosed herein to be exhibited at a high level.
[0042] The positive electrode active material layer 54 may further contain an additive component other than the positive electrode active material. Examples of the additive component include a conductive material, a binder, and trilithium phosphate. Examples of the conductive material include carbon black such as acetylene black (AB) and carbon materials such as graphite. Examples of the binder include fluorine-based resins such as polyvinylidene fluoride (PVdF).
[0043] Although not particularly limited, when the entire positive electrode active material layer 54 is taken as 100 mass%, the proportion of the positive electrode active material is preferably 70 mass% or more, more preferably 80 to 99 mass%, and even more preferably 85 to 98 mass%. The proportion of the conductive material is preferably 0.5 to 15 mass%, for example, 1 to 10 mass%, and more preferably 1 to 5 mass%. The proportion of the binder is preferably 0.5 to 15 mass%, for example, 0.8 to 10 mass%, and more preferably 1 to 5 mass%.
[0044] The negative electrode current collector 62 is strip-shaped. The negative electrode current collector 62 is preferably made of metal, and more preferably made of metal foil. Here, the negative electrode current collector 62 is copper foil. The negative electrode active material layer 64 contains a negative electrode active material. Examples of the negative electrode active material that can be used include Si-containing materials such as Si, SiO (silicon oxide), and SiC (silicon carbide), and carbon materials such as graphite, hard carbon, and soft carbon. The negative electrode active material layer 64 may contain an additive component other than the negative electrode active material. Examples of the additive component include a binder and a thickener. Examples of the binder include rubbers such as styrene butadiene rubber (SBR), and fluorine-based resins such as polyvinylidene fluoride (PVdF). Examples of the thickener include celluloses such as carboxymethyl cellulose (CMC).
[0045] The separator sheet 70 is in a strip shape. Examples of the separator sheet 70 include porous sheets (films) made of resins such as polyethylene (PE), polypropylene (PP), and polyester. Such porous sheets may have a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). A heat-resistant layer (HRL) may be provided on the surface of the separator sheet 70.
[0046] The nonaqueous electrolyte 80 is typically a nonaqueous electrolytic solution containing a nonaqueous solvent and a supporting salt (electrolyte salt). However, in other embodiments, it may be a polymer electrolyte. As the nonaqueous solvent, various organic solvents such as carbonates, ethers, and esters used in the electrolytic solutions of general nonaqueous electrolyte secondary batteries can be used alone or in appropriate combination of two or more. Specific examples include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC). As the supporting salt, for example, lithium salts such as LiPF6 and LiBF4 can be used.
[0047] The nonaqueous electrolyte secondary battery 100 can be used for various purposes, and because it combines high levels of input / output characteristics and cycle characteristics, it can be suitably used, for example, as a power source (driving power source) for a motor mounted on a vehicle such as a passenger car, a truck, etc. The type of vehicle is not particularly limited, and examples thereof include a plug-in hybrid electric vehicle (PHEV), a hybrid electric vehicle (HEV), and a battery electric vehicle (BEV).
[0048] Examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.
[0049] <Preparation of positive electrode active material> [Examples 1 to 7] In Examples 1 to 7, a Ni-containing lithium transition metal composite oxide having a coating layer formed thereon was prepared as a positive electrode active material. 1.04 Ni 0.83 Co 0.06 Mn 0.1 A particulate lithium nickel cobalt manganese composite oxide (NCM) represented by the formula (1) was prepared. Next, the Ni-containing lithium transition metal composite oxide and the coating oxide source shown in Table 1 were dry-mixed (mixing step). At this time, the mixing ratio was adjusted so that the coating layer after firing had a thickness shown in Table 1. For example, in Example 3, the mixing ratio of the Ni-containing lithium transition metal composite oxide and the coating oxide source was 1.00 mol:0.0005 mol. Then, the mixture was fired at 790° C. for 8 hours in an oxygen atmosphere to melt the coating oxide source and fuse the coating layer to the surface of the Ni-containing lithium transition metal composite oxide (firing step). In this manner, a positive electrode active material was obtained.
[0050] Reference Example In a reference example, the lithium nickel cobalt manganese composite oxide (NCM) having the above composition was used as it is as the positive electrode active material.
[0051] <Evaluation of positive electrode active material 1 (XPS)> XPS analysis was performed under the following conditions for the positive electrode active materials of Examples 1 to 3, 7 and Reference Example. Then, composition analysis of the measured elements was performed, and the amount (mol) of each element present in the region from the outermost surface to a depth of 10 nm was calculated. Using this value, the proportion (mol%) of Ni element was calculated from the following formula: {Ni / (W+Ni+Co+Mn)}×100. The results are shown in Table 1. In Table 1, "ND" indicates that the Ni element was below the lower detection limit. Equipment: PHI 5000 VersaProbe II (manufactured by ULVAC-PHI) X-ray source: AlKα monochromatic light Irradiation range: φ100μm HP(1400×200) Current / Voltage: 100W, 20kV
[0052] <Evaluation of positive electrode active material 2 (SEM-EDX)> The positive electrode active materials of Examples 1 to 3 and 7 and the Reference Example were subjected to SEM-EDX analysis. Specifically, a designated area (3 μm long × 3 μm wide) on the surface of the positive electrode active material was first observed with an SEM under the following conditions to obtain an SEM observation image. As an example, FIG. 3 shows a cross-sectional SEM observation image of the positive electrode active material of Example 1. Equipment: SU1000 (Hitachi Electron Microscope Systems) Acceleration voltage: 3~5kV Spot Intensity: 90 Focus distance: 10mm
[0053] Next, from the obtained SEM observation image, distance A and distance B were measured using image analysis software according to the following procedure, and the thickness of the coating layer (= distance A - distance B) was calculated. The results are shown in Table 1. Distance A: The distance from the center of the positive electrode active material to the surface of the coating layer. Distance B: The distance from the center of the positive electrode active material to the surface of the lithium nickel cobalt manganese composite oxide.
[0054] Next, a specified area of the obtained SEM observation image was subjected to EDX analysis under the following conditions, and elemental mapping was performed for each of the elements Ni, Co, Mn, and W, and the amount of each element present was calculated. Using this value, the proportion of Ni element (mol%) was calculated from the following formula: {Ni / (W+Ni+Co+Mn)}×100. The results are shown in Table 1. Note that "ND" in Table 1 indicates that the Ni element was below the lower detection limit. ·Device: JSM-7800 (manufactured by JEOL) Number of times: 3
[0055] <Preparation of lithium-ion secondary battery for evaluation> The positive electrode active material, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed in a mass ratio of positive electrode active material:AB:PVdF=100:1:1, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a positive electrode active material layer forming slurry. This positive electrode active material layer forming slurry was applied onto an aluminum foil (positive electrode current collector) and dried to form a positive electrode active material layer. Then, the positive electrode active material layer was roll-pressed with a rolling roller, and then cut to a predetermined size to prepare a positive electrode sheet.
[0056] In addition, a negative electrode active material (SiO) and graphite (C) were mixed with a styrene butadiene rubber (SBR) as a binder and a carboxymethyl cellulose (CMC) as a thickener in a mass ratio of (SiO+C):SBR:CMC=100:1:1, and an appropriate amount of ion-exchanged water was added to prepare a negative electrode active material layer forming slurry. This negative electrode active material layer forming slurry was applied onto a copper foil (negative electrode current collector) and dried to form a negative electrode active material layer. The negative electrode active material layer was then roll-pressed with a rolling roller, and then cut to a predetermined size to prepare a negative electrode sheet.
[0057] In addition, a porous polyolefin sheet having a three-layer structure of PP / PE / PP was prepared as a separator. Next, the positive electrode sheet and the negative electrode sheet were stacked with the separator interposed therebetween to prepare an electrode body. Next, an electrode terminal was attached to the electrode body, which was then inserted into a battery case made of an aluminum laminate film, and a non-aqueous electrolyte was poured into the electrode body. As the non-aqueous electrolyte, a mixed solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of EC:EMC=1:3, in which LiPF6 was dissolved as a supporting salt at a concentration of 1 mol / L, was used. Then, the battery case was sealed to obtain a lithium ion secondary battery for evaluation.
[0058] <Evaluation of initial characteristics (initial capacitance and initial resistance)> In an environment of 25°C, each lithium-ion secondary battery for evaluation was charged at a constant current of 0.1C to 4.2V, and then discharged at a constant current of 0.1C to 3.0V. The discharge capacity during constant current discharge was divided by the weight of the positive electrode active material to determine the initial discharge capacity (Ah / g). The results are shown in Table 1. In addition to the discharge capacity value, Table 1 also shows the following: "◎" when the initial discharge capacity was 190mAh / g or more, "◯" when the initial discharge capacity was 180mAh / g or more and less than 190mAh / g, and "×" when the initial discharge capacity was less than 180mAh / g.
[0059] Next, the battery was adjusted to a SOC of 50% in a 25°C environment, and after resting for 1 hour, it was discharged at a constant current of 5 C for 10 seconds. The initial resistance was calculated from the open circuit voltage (V0) immediately before discharge and the closed circuit voltage (V1) after 10 seconds of discharge using the following formula: resistance = (V0-V1) / current value at 5 C.
[0060] <Evaluation of cycle characteristics> Each lithium-ion secondary battery for evaluation was repeatedly charged and discharged at a constant current of 0.5C to 4.3V in an environment of 25°C, followed by constant current discharge at a discharge rate of 0.5C to 2.8V, with 100 cycles of high-rate charging and discharging. The discharge capacity after the cycle test was determined in the same manner as the initial discharge capacity. The results are shown in Table 1. The capacity retention rate (%) was calculated using the following formula: capacity retention rate = (discharge capacity after cycle test / initial discharge capacity) x 100. The results are shown in Table 1. In addition to the capacity retention rate value, Table 1 also shows the following: "◎" for 90% or more, "◯" for 85% or more and less than 90%, and "×" for less than 85%.
[0061] Next, the resistance after the cycle test was determined in the same manner as the initial resistance, and the resistance increase rate (%) was calculated by the following formula: resistance increase rate = [(resistance after cycle test - initial resistance) / initial resistance] x 100. The results are shown in Table 1. In addition to the resistance increase rate value, Table 1 also shows the following: "X" if it is 50% or more, "◯" if it is 31% or more and less than 50%, and "◎" if it is 31% or less.
[0062] [Table 1]
[0063] From the results in Table 1, in Reference Example and Example 1, the deterioration of battery characteristics after cycling was remarkable. Example 7 had a low initial discharge capacity. In contrast, in Examples 2 to 6, the initial discharge capacity was relatively high, and the deterioration of battery characteristics after cycling was suppressed. Such results demonstrate the technical significance of the invention disclosed herein.
[0064] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above.
[0065] For example, in the above embodiment, the Ni-containing lithium transition metal composite oxide and the coated oxide source are mixed by a dry mixing method, but this is not limited thereto. In another embodiment, the Ni-containing lithium transition metal composite oxide and the coated oxide source may be mixed by a wet mixing method. In this case, the (1) mixing step may include (1-1) a first mixing step, (1-2) a second mixing step, and (1-3) a drying step, in this order. In addition, other steps may be further included at any stage. For example, the (1-3) drying step may be followed by (1-4) a particle size adjustment step.
[0066] (1-1) In the first mixing step, an aqueous solution containing a first element source (typically a water-soluble ionic compound) is prepared. The aqueous solution can be prepared by dissolving the first element source (Co source and / or Mn source) in an aqueous solvent. The aqueous solvent is typically water, but may be a mixed solvent mainly composed of water. As a solvent other than water constituting the mixed solvent, an organic solvent that can be uniformly mixed with water, such as a lower alcohol or a lower ketone, can be used. The anion of the first element source can be appropriately selected so that the first element source is water-soluble, and can be, for example, an acetate ion, a sulfate ion, a nitrate ion, a carbonate ion, a hydroxide ion, a chloride ion, etc. Among them, the acetate ion is preferable. The concentration of the aqueous solution is preferably prepared so that the total of the first metal element (Co and / or Mn) is about 1 to 3 mol / L.
[0067] (1-2) In the second mixing step, a hydroxide is generated as a precursor on the surface of a particulate Ni-containing lithium transition metal composite oxide by a conventionally known crystallization method. Specifically, first, a particulate Ni-containing lithium transition metal composite oxide, an aqueous solution containing the first element source prepared above, and an alkaline compound of the second element are added to a reaction vessel to prepare a reaction liquid. As the alkaline compound, a compound containing a strong base (such as a hydroxide of an alkali metal) and / or a weak base (such as ammonia) and not inhibiting the generation of the hydroxide can be preferably used. A specific example is an ammonium salt of the second element. Among them, ammonium tungstate is preferable. It is preferable to prepare the ammonium ion concentration in the reaction liquid to be about 0 to 30 g / L, preferably 5 to 25 g / L, for example, 5 to 20 g / L.
[0068] Next, the prepared reaction solution is stirred and mixed under alkaline conditions (pH>7). Stirring and mixing can be performed, for example, by ultrasonic irradiation or a magnetic stirrer. The pH of the reaction solution is generally 10≦pH≦14, preferably 11≦pH≦14, for example, 11≦pH≦12. The stirring speed is generally 400 rpm or more, preferably 600 rpm or more, more preferably 800 rpm or more, for example, 1000 to 1500 rpm. As a result, a hydroxide containing the first element and the second element is precipitated (crystallized) on the surface of the particulate Ni-containing lithium transition metal composite oxide to obtain a precursor.
[0069] (1-3) In the drying step, after the precipitation of the hydroxide is completed, the precursor is isolated, washed, and then dried. Isolation can be performed by a conventionally known method, for example, a solid-liquid separation method such as centrifugation, filtration, decantation, or a spray drying method. The isolated precursor is then washed with water or the like to remove unreacted raw material compounds and impurities. Drying can be performed by a conventionally known method, for example, natural drying, heat drying, air drying, vacuum drying, or the like. The drying temperature is typically equal to or higher than the boiling point of the aqueous solvent, specifically, approximately equal to or lower than 100°C, for example, 60 to 100°C is preferable.
[0070] In the (1-4) particle size adjustment step, the particle size of the dried precursor is adjusted. In one example, the precursor aggregates are broken down by a conventionally known method. In another example, precursors of a predetermined particle size are selected through a sieve (a mesh member). The mixture obtained in this manner can be subjected to the (2) firing step of the above embodiment.
[0071] As described above, specific aspects of the technology disclosed herein include those described in the following sections. Item 1: A positive electrode active material comprising: a particulate Ni-containing lithium transition metal composite oxide; and a coating layer attached to at least a part of a surface of the Ni-containing lithium transition metal composite oxide, the coating layer including a composite oxide containing a first element selected from Co and Mn, and a second element belonging to Group 6, the coating layer having an average thickness of 50 nm or more and 200 nm or less based on cross-sectional observation with a transmission electron microscope. Item 2: The positive electrode active material according to item 1, wherein the coating layer is substantially free of Ni, and a region from an outermost surface of the positive electrode active material to a depth of 10 nm is measured by X-ray photoelectron spectroscopy, and when a total of a transition metal element contained in the Ni-containing lithium transition metal composite oxide and the first element and the second element contained in the coating layer is taken as 100 mol %, a proportion of Ni element in the region is 1 mol % or less. Item 3: The positive electrode active material according to item 1 or 2, wherein the coating layer is substantially free of Ni, and when an area of 3 μm length × 3 μm width on the surface of the positive electrode active material is observed with a scanning electron microscope and element mapping is performed with energy dispersive X-ray analysis, a proportion of Ni element within the area is 5 mol % or less when the total of the transition metal element contained in the Ni-containing lithium transition metal composite oxide and the first element and the second element contained in the coating layer is taken as 100 mol %. Item 4: The positive electrode active material according to any one of Items 1 to 3, wherein the Ni-containing lithium transition metal composite oxide is a lithium nickel cobalt manganese-based composite oxide. Item 5: The positive electrode active material according to any one of Items 1 to 4, wherein the first element is Co. Item 6: The positive electrode active material according to any one of Items 1 to 5, wherein the second element is W. Item 7: A non-aqueous electrolyte secondary battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode contains the positive electrode active material according to any one of items 1 to 6. Item 8: A method for producing a positive electrode active material, comprising: a mixing step of mixing a particulate Ni-containing lithium transition metal composite oxide with a compound containing a first element selected from Co and Mn and a second element belonging to Group 6 to obtain a mixture; and a firing step of firing the mixture in the presence of oxygen at a temperature of 500° C. or higher and 800° C. or lower. [Explanation of symbols]
[0072] 1 Cathode active material 2. Ni-containing lithium transition metal composite oxide 4 Covering layer 20 Electrode body 30 Battery case 50 Positive electrode sheet (positive electrode) 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 64 Negative electrode active material layer 70 Separator sheet 80 Non-aqueous electrolytes 100 Nonaqueous electrolyte secondary battery
Claims
1. A particulate Ni-containing lithium transition metal composite oxide; a coating layer attached to at least a portion of a surface of the Ni-containing lithium transition metal composite oxide; Equipped with The coating layer is An oxide including a first element selected from Co and Mn and a second element belonging to Group 6, The average thickness based on cross-sectional observation using a transmission electron microscope is 50 nm or more and 200 nm or less. Cathode active material.
2. The coating layer is substantially free of Ni, a region from the outermost surface of the positive electrode active material to a depth of 10 nm is measured by X-ray photoelectron spectroscopy, and in the region, when the total of the transition metal element contained in the Ni-containing lithium transition metal composite oxide and the first element and the second element contained in the coating layer is taken as 100 mol %, a proportion of Ni element is 1 mol % or less; The positive electrode active material according to claim 1 .
3. The coating layer is substantially free of Ni, A 3 μm×3 μm area on the surface of the positive electrode active material is observed with a scanning electron microscope, and element mapping is performed with energy dispersive X-ray analysis. In the observed area, when the total of the transition metal element contained in the Ni-containing lithium transition metal composite oxide and the first element and the second element contained in the coating layer is taken as 100 mol %, the proportion of Ni element is 5 mol % or less. The positive electrode active material according to claim 1 .
4. The Ni-containing lithium transition metal composite oxide is a lithium nickel cobalt manganese composite oxide. The positive electrode active material according to claim 1 .
5. The first element is Co; The positive electrode active material according to claim 1 .
6. The second element is W. The positive electrode active material according to claim 1 .
7. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, The positive electrode comprises the positive electrode active material according to any one of claims 1 to 3. Nonaqueous electrolyte secondary battery.
8. a mixing step of mixing a particulate Ni-containing lithium transition metal composite oxide with a compound containing a first element selected from Co and Mn and a second element belonging to Group 6 to obtain a mixture; A calcination step of calcining the mixture at a temperature of 500° C. or more and 800° C. or less in the presence of oxygen; A method for producing a positive electrode active material comprising the steps of:
Citation Information
Patent Citations
Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, and nonaqueous electrolyte secondary battery including the positive electrode active material
JP2013125732A
Positive electrode active material and lithium ion secondary battery
JP2017183045A
Method for preparing positive electrode active material for rechargeable battery
JP2024501509A
Method for preparing a positive electrode active material for rechargeable batteries
WO2022130312A1
Method of manufacturing positive electrode active material, and positive electrode active material
JP2010040383A